Increased Pentraxin 3 Levels Correlate With IVIG Responsiveness and Coronary Artery Aneurysm Formation in Kawasaki Disease - Kitoh, Toshiyuki; Ohara, Tsuyoshi; Muto, Taichiro; Okumura, Akihisa; Baba, Reizo; Koizumi, Yusuke; Yamagishi, Yuka; Mikamo, Hiroshige; Daigo, Kenji; Hamakubo, Takao (Frontiers in Immunology, 2021)
Kawasaki disease (KD) is a febrile disease of childhood characterized by systemic vasculitis that can lead to coronary artery lesions (CAL). This was a prospective cohort study to determine the levels of the pentraxin 3 (PTX3), soluble CD24-Subtype (Presepsin) and N-terminal pro-brain natriuretic peptide (NT-pro BNP) in consecutive KD patients. From January 2013 to March 2015, all patients with KD admitted to Aichi Medical University Hospital who provided consent had their plasma saved before IVIG administration. In total, 97 cases were registered. 22 cases of incomplete KD were excluded from the outcome analysis. In the 75 total cases used for statistical analyses. A PTX3 threshold of >7.92 ng/ml provided a specificity of 88.5 %, a sensitivity of 94.4 %, and a likelihood ratio as high as 15.92 for the diagnosis of KD compared with febrile non-KD controls. Although an echocardiographic diagnosis of CAL in the early course of the disease was confirmed in 24 cases, it was not in the remaining 51 cases. Neither NT-proBNP nor Presepsin had statistical significance for the prediction of the echocardiographic CAL diagnosis. Only PTX3 was significantly predictive of the echocardiographic CAL diagnosis (p=0.01). The PTX3 level was significantly higher in the intravenous immunoglobulin (IVIG) non-responders (45.9±7.45) than in the IVIG responders (17.0±1.46 ng/ml) (p< 0.001). The PTX3 level also correlated with the number of IVIG treatment courses needed to resolve fever (R² =0.64). Persistent CAL (pCAL) formation was observed in three cases; one of aneurysm only and two aneurysms with dilatations. The patients with pCAL had significantly higher PTX3 levels (85 ± 8.4 ng/ml) than patients without pCAL (22 ± 2.2 ng/ml) (p< 0.0001). In terms of pCAL prediction, the Area under the curve (AUC) of receiver operating characteristic ROC curve of PTX3 was 0.99, and it was significantly greater than that of Presepsin (0.67) or NT-proBNP (0.75). PTX3 is a soluble pattern recognition molecule that acts as a main component of the innate immune system. These data suggest that PTX3 can be utilized as a definitive biomarker for the prediction of IVIG resistance and subsequent CAL formation in patients with KD.